Analisis manajemen risiko pada platform Peer to Peer Lending dalam mendukung keberlanjutan Startup Fintech - Ningsih, Anggun Wahyuni (Maliki Interdisciplinary Journal, 2025)
This research discusses risk management analysis on the Peer to Peer Lending (P2P Lending) platform in supporting the sustainability of fintech startups. This research uses a qualitative method with a library research approach, by reviewing various sources such as scientific journals, regulatory reports, and publications from relevant authorities. P2P Lending is a digital financial service innovation that brings together fund providers and recipients through a technology platform. Despite providing easy access to capital, P2P Lending faces complex risk challenges, such as credit risk, operational risk, regulatory risk, and liquidity risk. The analysis shows that mitigation strategies such as credit scoring, credit insurance, cybersecurity enhancement, and regulatory compliance can support the sustainability of fintech startups. This research emphasizes the importance of a comprehensive risk management system to increase investor confidence and strengthen fintech's contribution to financial inclusion in Indonesia.